Transition into Distance Education: A Scoping Review - Roxana Schweighart; Michael Hast; Anna Maria Pampel; Julian Alexander Rebien; Caroline Trautwein (MDPI AG, 2024)
The number of students enrolling in distance learning programmes is rising worldwide, making distance education (DE) a significant part of higher education (HE). Transitioning into a study programme involves numerous challenges, especially for distance learners who face higher dropout rates and compromised academic performance compared to traditional on-campus students. However, when students master these challenges, study success becomes more likely. Nevertheless, knowledge about transitioning into DE remains limited. This scoping review aims to compile existing knowledge and enhance understanding of the critical initial phase of DE by answering the research question: "What is known about the transition into DE in HE?". Following the methodological steps outlined in the PRISMA-ScR checklist, we identified 60 sources from five databases, meeting inclusion criteria through a multi-stage screening process. These articles were analysed using qualitative content analysis. We developed a category system with 12 main categories: 1. Process of transition into DE; 2. Reasons for choosing DE; 3. Characteristics of distance learners; 4. Academic success and failure; 5. General assessment of DE; 6. Differences between face-to-face and DE; 7. Advantages of DE; 8. Challenges of DE; 9. Critical life events; 10. Coping strategies; 11. Add-on initiatives; and 12. Recommendations for DE. The results underline the complexity of the transition into DE, which has unique patterns for each student. The article concludes with practical implications and recommendations for supporting the transition into DE.